Apa yang dapat kita pelajari dari tesis MPH: pengalaman dari Universitas Gadjah Mada - Dian Mawarni; Riris Andono Ahmad; Mubasysyir Hasanbasri (Berita Kedokteran Masyarakat (BKM), 2016)
What do MPH student theses tell us? Experience from Universitas Gadjah MadaPuposeThis study aimed to evaluate MPH professional performance through thesis writing. MethodWe review 103 MPH student theses in health policy and management tract from data library of Faculty of Medicine Universitas Gadjah Mada since 2013 to 2015. We extract topic and reference from each thesis with a questionnaire.ResultsSeventy percent of students choose subject relevant to health policy and management tract. Sixty percent of theses are located in quadrant 3 because they have relevant topic but weak on use of appropriate reference. Only several journals in health policy and management are cited in theses such as health policy and planning, health policy, BMC health services research and human resources for health. More references related to other multidisciplines and published over 5 years. ConclusionMPH students are in need of clear understanding of the domain and scope of work they are interested in. Their theses showed limited evidence about references focus that has practical relevance to their future work or to the job they currently have.